Chemical variables - stream from Följesjön, S-stream-8 - Skogaryd Research Catchment (University of Gothenburg, 2024)
Manual grab samples from the stream for chemical analysis are taken on a biweekly basis during ice-free conditions, and on a monthly basis in the presence of stream ice.
Skogaryd Research Catchment (2024). Chemical variables - stream from Följesjön, S-stream-8, 2020-01-14–2022-11-16 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/Y958ZFS2HcXWLLr733TwNuMW
Keywords: Skogaryd Research Catchment; Stream; Time instant; Time instant; Electrical conductivity; Electrical conductivity; Water temperature; Water temperature; pH; pH; Reference Water temperature for pH measurement; Reference Water temperature for pH measurement; Dissolved organic carbon; Dissolved organic carbon; Total nitrogen; Total nitrogen; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrite-N/Nitrate-N; Nitrite-N/Nitrate-N; Fluorine; Fluorine; Bromine; Bromine; Chlorine; Chlorine; Boron; Boron; Sodium; Sodium; Magnesium; Magnesium; Aluminium; Aluminium; Silicon; Silicon; Phosphorus; Phosphorus; Sulfur; Sulfur; Potassium; Potassium; Calcium; Calcium; Manganese; Manganese; Iron; Iron; Zinc; Zinc; Absorbance; Absorbance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap